2022
DOI: 10.3390/molecules27238446
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated and Non-Fluorinated 1,4-Diarylpyrazoles via MnO2-Mediated Mechanochemical Deacylative Oxidation of 5-Acylpyrazolines

Abstract: A solvent-free two-step synthesis of polyfunctionalized pyrazoles under ball-milling mechanochemical conditions was developed. The protocol comprises (3 + 2)-cycloaddition of in situ generated nitrile imines and chalcones, followed by oxidation of the initially formed 5-acylpyrazolines with activated MnO2. The second step proceeds via an exclusive deacylative pathway, to give a series of 1,4-diarylpyrazoles functionalized with a fluorinated (CF3) or non-fluorinated (Ph, COOEt, Ac) substituent at C(3) of the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…They have also shown that, in contrast, the MnO 2 -mediated oxidation of a model isomeric 4-acylpyrazoline proceeded with low chemoselectivity, leading to fully substituted pyrazole as a major product formed via dehydrogenative aromatization. This work also evidenced the application of nitrile imines as building blocks for organic synthesis [2]. R. Jasi ński and coworkers used molecular electron density theory (MEDT) to explain the unexpected formation of 1-(4-bromophenyl)-3-phenyl-5-nitropyrazole in the reaction between (E)-3,3,3-trichloro-1-nitroprop-1-ene and N-(4-bromophenyl)-C-arylnitrylimine.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…They have also shown that, in contrast, the MnO 2 -mediated oxidation of a model isomeric 4-acylpyrazoline proceeded with low chemoselectivity, leading to fully substituted pyrazole as a major product formed via dehydrogenative aromatization. This work also evidenced the application of nitrile imines as building blocks for organic synthesis [2]. R. Jasi ński and coworkers used molecular electron density theory (MEDT) to explain the unexpected formation of 1-(4-bromophenyl)-3-phenyl-5-nitropyrazole in the reaction between (E)-3,3,3-trichloro-1-nitroprop-1-ene and N-(4-bromophenyl)-C-arylnitrylimine.…”
mentioning
confidence: 81%
“…They also examined and discussed the influence of an additional substituent at the 7-position on the biological and optical properties of the compounds [8]. A. Šačkus, E. Arbačiauskien ė and coworkers developed a simple and efficient synthetic route for the preparation of 3a,4-dihydro-3H,7H-and 4H,7H-pyrazolo [4 ,3 :5,6]pyrano [4,3-c] [1,2]oxazoles from easily obtainable 3-(prop-2-en-1-yloxy)-or 3-(prop-2-yn-1-yloxy)-1H-pyrazole-4-carbaldehydes via the intramolecular nitrile oxide cycloaddition (INOC) reaction of intermediate oximes. The key step is the nitrile oxide preparation from the corresponding aldoximes, which was carried out via oxidation with sodium hypochlorite.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the final product is produced via the spontaneous elimination of an alcohol molecule from the initially formed (3+2)-cycloadduct. Further studies on 1,3-dipolar cycloadditions of 1 onto C=C and C≡C bonds using nitroolefins [ 33 ], cyanoalkenes [ 34 ], enones [ 35 , 36 , 37 ], alkoxyallenes [ 28 ], and benzynes [ 30 ] as dipolarophiles also evidenced the high synthetic potential of CF 3 -nitrile imines in the synthesis of pyrazoline and pyrazole derivatives. The addition of 1 with hetero-dipolarophiles are also known ( Scheme 1 b); a series of thiocarbonyl compounds including (cyclo)aliphatic [ 26 , 38 ], aromatic, and ferrocenyl thioketones [ 25 ], as well as thiochalcones [ 39 ] and thioamides [ 40 ], smoothly reacted with trifluoroacetonitrile imines 1 to afford 1,3,4-thidiazole derivatives of type 3 formed as the exclusive products.…”
Section: Introductionmentioning
confidence: 99%
“…Among the methods available to date, classical condensation of trifluoromethylated 1,3-dicarbonyls or their equivalents with hydrazines is the most often applied strategy to access 3-trifluoromethylpyrazoles. , Also, (3 + 2)-cycloadditions of fluorinated 1,3-dipoles such as 2,2,2-trifluorodiazoethane (CF 3 CHN 2 ) with appropriate dipolarophiles have been shown to be a powerful approach . Importantly, rapid progress in the chemistry of trifluoroacetonitrile imines 1 (Scheme ), recognized as readily available building blocks for the preparation of 3-CF 3 -pyrazoles, has been observed in recent years. , Notably, application of this 1,3-dipole, readily accessible in situ via base-mediated dehydrohalogenation of the respective hydrazonoyl halides 2 , leads to N-functionalized heterocycles and typically offers excellent control on regio- and chemoselectivity of the cycloaddition step. For example, either electron-rich (vinyl ethers, enamines, and benzynes) or electron-deficient dipolarophiles (e.g., cyanoalkenes, nitroolefins, and enones) have been demonstrated as suitable reaction partners to access polyfunctionalized products.…”
mentioning
confidence: 99%